Simulating Semiclassical Black Holes - Berczi, Benjamin (2024)
In this thesis the first attempts to study the real-time dynamics of semiclassical gravitational collapse and semiclassical black holes are presented. Specifically, the chosen system is a massless quantum scalar field coupled to Einstein gravity in spherical symmetry in four dimensions. The semiclassical system is built using a coherent state as the chosen quantum state, which enables the semiclassical simulations to connect to classical ones. Thus, the existing literature of classical collapse can be utilised and semiclassical simulations can be built upon them. The quantum field is regularised using dynamical Pauli-Villars fields. This formalism is ideal to study semiclassical gravitational collapse and critical phenomena, as well as correlation functions to look for signals of Hawking radiation.